Respiratory frequency as a marker of physical effort during high-intensity interval training in soccer players - Nicolò, A.; Montini, M.; Girardi, M.; Felici, F.; Bazzucchi, I.; Sacchetti, M. (International Journal of Sports Physiology and Performance, 2020)
Purpose: Variables currently used in soccer training monitoring fail to represent the physiological demand of the player during movements like accelerations, decelerations, and directional changes performed at high intensity. We tested the hypothesis that respiratory frequency (fR) is a marker of physical effort during soccer-related high-intensity exercise. Methods: A total of 12 male soccer players performed a preliminary intermittent incremental test and 2 shuttle-run high-intensity interval training (HIIT) protocols, in separate visits. The 2 HIIT protocols consisted of 12 repetitions over 9 minutes and differed in the work-to-recovery ratio (15:30 vs 30:15 s). Work rate was self-paced by participants to achieve the longest possible total distance in each HIIT protocol. Results: Work-phase average metabolic power was higher (P<.001) in the 15:30-second protocol (31.7 [3.0] W/kg) compared with the 30:15-second protocol (22.8 [2.0] W/kg). Unlike heart rate and oxygen uptake, fR showed a fast response to the work-recovery alternation during both HIIT protocols, resembling changes in metabolic power even at supramaximal intensities. Large correlations (P<.001) were observed between fR and rating of perceived exertion during both 15:30-second (r=.87) and 30:15-second protocols (r=.85). Conclusions: Our findings suggest that fR is a good marker of physical effort during shuttle-run HIIT in soccer players. These findings have implications for monitoring training in soccer and other team sports.